A multiplex PCR assay for detection of Vibrio vulnificus, Aeromonas hydrophila, methicillin-resistant Staphylococcus aureus, Streptococcus pyogenes, and Streptococcus agalactiae from the isolates of patients with necrotizing fasciitis. (April 2019) - Tsai, Yao-Hung; Chen, Po-Han; Yu, Pei-An; Chen, Chi-Lung; Kuo, Liang Tseng; Huang, Kuo-Chin
Highlights: This article describes a DNA array-based analysis of multiplex PCR-amplified gene segments of five lethal microorganisms that were present in tissue samples obtained from patients with necrotizing fasciitis, and not from seafood samples or environmental strains. The multiplex PCR assay presented negative results for all 99 blood samples; however, positive PCR results were found for 28 tissue specimens. The multiplex PCR of tissue specimens may be a useful and rapid diagnostic tool for the detection of these lethal microorganisms in patients with necrotizing fasciitis. Abstract: Background: Vibrio vulnificus, Aeromonas hydrophila, methicillin-resistant Staphylococcus aureus (MRSA), group A Streptococcus, and group B Streptococcus are commonly detected causative agents of necrotizing fasciitis (NF) in Chia-Yi Chang Gung Memorial Hospital. The aim of this study was to develop and evaluate a multiplex PCR method for the simultaneous detection of five of the most important human pathogens involved in NF by using a novel combination of species-specific genes. Methods: The samples used were collected from 99 patients with surgically confirmed NF of the extremities who were hospitalized consecutively between June 2015 and November 2017. Two sets of blood and tissue samples were collected from all patients; one set was sent to a microbiology laboratory for bacterial identification and the other set was sent to an immunohistochemistry laboratory for PCR amplification. Results: The multiplex PCR results for the blood samples showed negative findings. The multiplex PCR results for the tissue specimens showed 28 positive findings. Fourteen (87.5%) of the 16 V. vulnificus culture-positive tissue specimens, six (75%) of the eight A. hydrophila culture-positive tissue specimens, and four (100%) of the four MRSA culture-positive tissue specimens were positive by PCR. Similarly, two (100%) of the group A Streptococcus and two (100%) of the group B Streptococcus were PCR-positive. Conclusions: The accuracy rate of the multiplex PCR presenting positive results in these culture-positive tissue samples was 87.5% (28/32). This suggests that multiplex PCR of tissue specimens may be a useful and rapid diagnostic tool for the detection of these lethal microorganisms in patients with NF.